Investigation of the Effect of Sealer Use on the Heat Generated at the External Root Surface during Root Canal Obturation Using Warm Vertical Compaction Technique with System B Heat Source - Viapiana, Raqueli [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP]; Camilleri, Josette (Elsevier B.V., 2014)
Introduction: During warm vertical compaction of gutta-percha, root canal sealers with different chemical compositions absorb the heat generated inside the root canal. The aim of this research was to assess physicochemical modifications of sealers subjected to the System B heat source (Analytic Technology, Redmond, WA) and to evaluate the effect that the use of different sealers has on the heat transfer to the external root surface. Methods: Three proprietary brand sealers (AH Plus [Dentsply International, Addlestone, UK], Pulp Canal Sealer [Kerr Corporation, Orange, CA], MTA Fillapex [Angelus Dental Solutions, Londrina, PR, Brazil]) and a prototype sealer based on Portland cement were assessed. The heat generated on the surfaces of System pluggers and the heat dissipation at different levels (apical, midroot, and cervical) over root surface while using different sealers was assessed using thermocouples. Data were collected in 3 different environmental conditions with the tooth suspended in air, immersed in Hank's balanced salt solution, or gelatinized Hank's balanced salt solution. Chemical changes in the sealers induced by the heat were monitored by Fourier transform infrared spectroscopy. The effect of heat changes on the setting time and compressive strength of the sealers was also assessed. Results: The continuous wave plugger sustained a rise in temperature at a maximum of 80 C at the instrument shank. The highest change in temperature on the external root surface was recorded after 1.5 minutes from the start of heating, and it was restored to body temperature by 6 minutes. Environmental conditions affected heat dissipation for all the sealers in the midroot and cervical regions and the highest increase in temperature (similar to 60 degrees C) recorded in air. In the midroot and cervical regions, the type of sealer used did not affect the rise in temperature. In the apical region, AH Plus obturations resulted in a greater rise in temperature, and the chemical composition of this sealer was affected by high temperature; it also induced a reduction in sealer setting time and strength. Conclusions: It could be concluded that surrounding conditions, such as temperature and humidity, exerted influence on heating dissipation during the continuous wave of the condensation obturation technique and that root canal sealers presented different conductive/isolating properties. Furthermore, the physical and chemical properties of AH Plus were negatively affected by the changes in temperature.
Keywords: Characterization; endodontics; physical properties; root canal obturation; System B